2014
DOI: 10.3390/proteomes2020169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminum Treatment on Proteomes of Radicles of Seeds Derived from Al-Treated Tomato Plants

Abstract: Aluminum (Al) toxicity is a major constraint to plant growth and crop yield in acid soils. Tomato cultivars are especially susceptible to excessive Al3+ accumulated in the root zone. In this study, tomato plants were grown in a hydroponic culture system supplemented with 50 µM AlK(SO4)2. Seeds harvested from Al-treated plants contained a significantly higher Al content than those grown in the control hydroponic solution. In this study, these Al-enriched tomato seeds (harvested from Al-treated tomato plants) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 55 publications
(60 reference statements)
0
34
0
Order By: Relevance
“…Activation time for HCD analysis was 0.1 min. All data were acquired using XCalibur 2.1 (Thermo-Fisher Scientific) [18,24]. Proteins were identified using the MS data to query the switchgrass annotated database () via Mascot v2.3.02 (Matrix Sciences, Boston, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Activation time for HCD analysis was 0.1 min. All data were acquired using XCalibur 2.1 (Thermo-Fisher Scientific) [18,24]. Proteins were identified using the MS data to query the switchgrass annotated database () via Mascot v2.3.02 (Matrix Sciences, Boston, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The peptide separation was accomplished using an Acquity UPLC System and UV detection (Waters, Milford, MA) coupled with a robotic fraction collector (Probot; Dionex, Sunnyvale, CA, USA) as reported previously (Okekeobu et al, 2014). Specifically, the iTRAQ 8-plex tagged tryptic peptides were reconstituted in buffer A (20 mM ammonium formate pH 9.5 in water), and half of the sample was loaded onto an Acquity UPLC BEH C18 column (1.7 μm, 2.1 × 100 mm, Waters, Milford, MA) with 20 mM ammonium formate (NH4FA), pH 9.5 as buffer A and 90% ACN/10% 20 mM NH4FA as buffer B.…”
Section: Methodsmentioning
confidence: 99%
“…The Sorghum bicolor protein RefSeq sequence database containing 75,079 sequence entries was downloaded on 9 Dec, 2014 from NCBInr and used for database searches. The default search settings used for 8-plex iTRAQ quantitative processing and protein identification in Mascot server were as described previously (Yang Y. et al, 2011; Okekeobu et al, 2014). In brief, two miss-cleavage for full trypsin digestions were conducted with fixed methylthio modification of cysteine, fixed 8-plex iTRAQ modifications on lysine and N-terminal amines and variable modifications of methionine oxidation and deamidation on asparagines/glutamine residues.…”
Section: Methodsmentioning
confidence: 99%
“…Tomato is sensitive to Al toxicity [9,10,11] at both the vegetative and reproductive stages. Previous studies have shown that Al treatments induced global changes in proteome expression in roots, leaves, fruits and seeds in tomato [12,13,14]. These molecular responses are mobilized to deal with Al 3+ ion toxicity, as well as the Al-induced interferences in plant mineral nutrition [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics analysis has proven to be a very powerful tool in revealing the relative abundance of proteins or the identification of individual proteins related to specific cell functions in plants [24,25,26]. More importantly, our previous studies have shown that Al treatments affected proteome composition, not only in roots, but also in the aboveground tissues, including leaves, cotyledons, seeds and germinating radicles derived from the Al-treated seeds [12,25,26]. …”
Section: Introductionmentioning
confidence: 99%